PATTERNS OF INJURIES AND PSYCHOLOGICAL TRAUMA IN DOMESTIC VIOLENCE PATIENTS: A SYSTEMATIC LITERATURE REVIEW - Gizela, Beta Ahlam; Liliana, Belinda (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Background: Domestic violence is a complex problem that occurs in various countries in the world. It is noted that women are more often being victims of domestic violence, 1 of 4 women and 1 of 9 men in the world experiencing domestic violence. The number of cases tends to increase from year to year. Domestic violence is bad for the health of victims, both physically and psychologically. Doctors need certain methods to identify domestic violence, include pattern of injuries and psychological trauma of the victims that can be found through physical and mental examination. Aim: To describe the pattern of injuries and psychological trauma experienced by domestic violence patients, and to find corelation between demographic factors of age, gender, and race to the pattern of injuries and psychological trauma. Method: The study is a systematic literature review by analysing literature obtained from databases with specific criteria and keywords about patterns of injuries and psychological trauma in domestic violence patients as well as their association with demographic factors of age, gender, and race. Researchers will explore information from the literature found through the processes of abstraction, analysis, and data synthesis. Result: Based on searches of four electronic databases PubMed, Scopus, ScienceDirect, and EBSCOHost, 241 journals were obtained. After screening through the title, abstract, and exclusive journal, obtained 11 journals. Based on the 11 journals, results were obtained in the form of wound patterns, which include the number, location, and type of wounds; psychological trauma; as well as the corelation of demographic factors, which include age, gender, and race, to pattern of injuries and psychological trauma in domestic violence patients. Conclusion: The location of the most common injuries in domestic violence patients is the head, neck, and face. The most common type of injury found in domestic violence patients is bruising with most experiencing a greater number of injuries. The most common psychological trauma experienced by domestic patients is depression and PTSD. Racial differences had no effect on differences in wound patterns. But in the pattern of psychological trauma, Caucasians have higher rates of PTSD and depression than African-Americans.